2007
DOI: 10.1021/jp070638y
|View full text |Cite
|
Sign up to set email alerts
|

Computational Studies of Electron Paramagnetic Resonance Parameters for Paramagnetic Molybdenum Complexes. 1. Method Validation on Small and Medium-Sized Systems

Abstract: A variety of density functional methods have been evaluated in the computation of electronic g-tensors and molybdenum hyperfine couplings for systems ranging from the Mo atom through MoIIIN, [MoVOCl4]-, and [MoVOF5]2- to two larger MoV complexes MoXLCl2 (X=O, S; L=tris(3,5-dimethylpyrazolyl)hydroborate anion). In particular, the influence of the molybdenum basis set and of various exchange-correlation functionals with variable admixtures of Hartree-Fock exchange on the computed EPR parameters have been evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
68
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(79 citation statements)
references
References 82 publications
10
68
1
Order By: Relevance
“…In case of Mo V and W V sites, metal and ligand hyperfine couplings, certain ligand nuclear quadrupole couplings, and the electronic g-tensor, are the most important parameters to be considered to describe the EPR spectra [14][15][16]25]. We have recently validated state-of-the-art quantum chemical approaches based on density functional theory (DFT) for the calculation of g-tensors and Mo hyperfine tensors in a series of Mo(V) complexes ranging from small models to larger complexes of low symmetry that resemble some of the enzyme active sites [26,27]. It turned out that hybrid functionals with an exact-exchange admixture between 30% and 40% provided the best agreement with experimental g-and hyperfine tensors, including the orientations of these tensors relative to each other and to the molecular framework (as compared to single crystal EPR data with 95 Mo and 97 Mo isotope-enriched samples) [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of Mo V and W V sites, metal and ligand hyperfine couplings, certain ligand nuclear quadrupole couplings, and the electronic g-tensor, are the most important parameters to be considered to describe the EPR spectra [14][15][16]25]. We have recently validated state-of-the-art quantum chemical approaches based on density functional theory (DFT) for the calculation of g-tensors and Mo hyperfine tensors in a series of Mo(V) complexes ranging from small models to larger complexes of low symmetry that resemble some of the enzyme active sites [26,27]. It turned out that hybrid functionals with an exact-exchange admixture between 30% and 40% provided the best agreement with experimental g-and hyperfine tensors, including the orientations of these tensors relative to each other and to the molecular framework (as compared to single crystal EPR data with 95 Mo and 97 Mo isotope-enriched samples) [26].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently validated state-of-the-art quantum chemical approaches based on density functional theory (DFT) for the calculation of g-tensors and Mo hyperfine tensors in a series of Mo(V) complexes ranging from small models to larger complexes of low symmetry that resemble some of the enzyme active sites [26,27]. It turned out that hybrid functionals with an exact-exchange admixture between 30% and 40% provided the best agreement with experimental g-and hyperfine tensors, including the orientations of these tensors relative to each other and to the molecular framework (as compared to single crystal EPR data with 95 Mo and 97 Mo isotope-enriched samples) [26]. In cases of X-band powder spectra without isotope enrichment, the hyperfine tensors of model complexes and enzymes frequently cannot be determined accurately by experiment, and it was shown that assistance by quantum chemical calculations may allow improved spectra simulations in such cases [27].…”
Section: Introductionmentioning
confidence: 99%
“…While B3 LYP is clearly the most popular functional in main group chemistry (albeit it also has been shown to exhibit severe shortcomings even in organic chemistry), it appears that the optimum amount of exact-exchange admixture varies for different systems and different properties (see, e.g., discussions in refs. [27,64,[66][67][68][69][70][71][72]). B3 LYP incorporates 20 % and the BHLYP functional 50 % HF exchange, and thus a comparison of these two hybrid functionals with the BP86 and BLYP GGA functionals should provide insight to an interrelation between charge transfer between metal and bridging ligand (and vice versa) and the computed features in 5 2…”
mentioning
confidence: 99%
“…For subsequent analyses, single-point calculations on the model structure 1 cs were performed at B3LYP/TZVP level by using a TZVP-based 12s6p5d all-electron basis set for Mo. [30] For all single-point calculations the Gaussian 03 program package [31] was used. NPA analyses and calculation of Wiberg bond indices for all complexes under consideration (1, 2, 8, 9) were performed with the NBO program (version 3.1) [32] as part of the Gaussian 03 program package.…”
Section: Wwwchemeurjorg Experimental Sectionmentioning
confidence: 99%